Effect of Pictures and Writing of Smoking Health Warnings on Adolescent Smokers’ Behavior - Bagea, Ishak; Sulistiani, Indah; Judijanto, Loso; Safar, Muh.; Amir, Andi Subhan; Yuniarti, Elsa (Migration Letters, 2024)
Smoking has become a habit among adults, even teenagers who are still in their teens already understand how to smoke. To reduce the death rate of smokers or teenagers in the future, the Indonesian Ministry of Health has made various efforts to warn the public about the dangers of smoking to health. Warnings are given in the form of pictures and writing. Quantitative research using the linear regression method. The population is all existing students at Muhammadiyah Middle School 9, Biringkanaya District. The sample used was 135. Instrument study questionnaire in the form of a list of questions via a Likert scale. Research results show Pictures are also influential positive and significant to demonstrated adolescent behavior with mark test results Q of T count 3,760 > 1,978 T table And p-value 0.000 < 0.05. W riting effect positive and significant in a manner Partial to adolescent behavior from results T count 9,555 > 1,978 T table And p-value 000. Pictures and writing influential positive and significant in a manner simultaneous to variable bound adolescent behavior ari result F count 71,771 > F table 3.07 and 0.000 <0.05. Influence to two variable pictures and writing to variable adolescent behavior by 44.1% and 5.9 % influenced leh other factors outside research.